PALLADIUM AND GOLD MINERALS FROM THE BARONSKOE-KLUEVSKY ORE DEPOSIT (VOLKOVSKY COMPLEX, CENTRAL URALS, RUSSIA) - Zaccarini F.; Anikina E.; Pusharev E.; Rusin I.; Garuti G. (My University, 2004)
Drill cores from the newly discovered Baronskoe-Kluevsky Pd–Au deposit (Volkovsky massif, Central Urals) have been investigated by reflected-light and electron microscopy, and the ore minerals were analyzed by electron microprobe. The most abundant Platinum-group mineral (PGM) is vysotskite, ideally PdS, characterized by an unusual Pt,Ni-poor composition. Palladium also occurs in kotulskite (PdTe), stillwaterite (Pd8As3), and unknown Pd–As–Te compounds with vincentite-type Pd3(As,Te), stillwaterite-type Pd8(As,Te)3, and Pd7(As,Te)2 stoichiometries. The main carrier of Au is Pd-rich electrum, approaching the composition Au75Ag15Pd10, with minor Fe, Cu, Ni and Pt. The precious minerals are closely associated with minute blebs of chalcopyrite+magnetite disseminated throughout serpentinized olivine-apatite host rock. Paragenetic relationships among the ore minerals define a succession of crystallization events in the order: 1) Cu–Pd sulfides+electrum, 2) replacement by Pd–Te–As and late Pd–As PGM, 3) final replacement by magnetite. The paragenesis is tentatively related with cooling of a fluid phase in the late- to post-magmatic stage.